PROGRESIVE QUR’ANIC STUDIES IN INDONESIAN STATE ISLAMIC HIGHER EDUCATION (2014-2019): IMPLEMENTATION AND DEVELOPMENT - Maizuddin Maizuddin; Zulihafnani Zulihafnani (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2021)
This article describes the state of progressive Qur'anic interpretation studies over the past five years at three State Islamic Higher Education, UIN Ar-Raniry Banda Aceh, UIN Imam Bonjol Padang and UIN Sultan Syarif Kasim Riau. The article is based on the argument that the study of the progressive interpretation of the Qur'an which is reflected in the issues of social justice, women and gender equality, pluralism, and deradicalization has strong relevance to contemporary issues that are widely discussed by scholars. In addition, it is also the responsibility of Islamic higher education to provide Qur'anic solutions to the contemporary problems. The study focused on three questions, namely: the frequency of progressive interpretation studies, the concentration of progressive interpretation issues, and the development and orientation of progressive interpretation studies. The method used in this study is a literature review of the scientific publications of lecturers in the study of the Koran and the final papers of students majoring in Al-Qur'an and Tafsir. The results showed that the study frequency of progressive Qur'anic interpretation in the three universities in the period 2014 – 2019 was still low, recorded at 18.52%. However, the frequency  of progressive Qur'anic studies in the 2014-2019 period showed an increase of 1.3%. The issues discussed have covered the four issues mentioned above, although some of them have not received enough attention. The orientation of the study is still concentrated on the interpretation of the meaning of the Koran, it has not yet led to a methodological study in building a paradigm and approach to contemporary interpretation. Keywords: progressive exegesis; frequency; issues; development and orientation of the study